Submicron-scale experimental analyses of multi-asperity contacts with different roughnesses. (March 2018) - Zugelj, B. Brodnik; Kalin, M.
Abstract: The multi-asperity contacts between two nominally flat surfaces were studied experimentally with sub-micron resolution, to provide detailed experimental information that is seriously lacking today. The relationships between the contact pressure, the real contact area and the deformation of asperities were investigated for realistic steel specimens with different roughness in the full engineering loading range up to the material's macro yield stress ( Y ). For the rough surfaces the real contact area increases almost linearly with slight decay at 0.35· Y as the load increases, and reaches 20% of nominal contact area at yield stress. This decay in real contact area growth is very obvious at 0.55· Y for smooth surface that reaches 10% of nominal contact area at yield stress. Deformation of all asperities is increasing with roughness. However, for rough surfaces the deformation is constantly increasing with load, while for the smooth surface the deformation of the asperities severely decreases when the nominal contact pressure reaches about 0.4∙ Y . Highlights: The multi-asperity contacts between two nominally flat surfaces were studied experimentally with submicron resolution. Realistic steel specimens with relevant engineering roughnesses were tested. The relationships between the contact pressure, the real contact area and the asperity deformation were investigated. Experimental results were compared to the most commonly used elastic-plastic statistical multi-asperity contact models.